CHI3L1 results in poor outcome of ovarian cancer by promoting properties of stem-like cells. Issue 1 (January 2019) - Lin, Han-Wei; Chiang, Ying-Cheng; Sun, Nai-Yun; Chen, Yu-Li; Chang, Chi-Fang; Tai, Yi-Jou; Chen, Chi-An; Cheng, Wen-Fang
Abstract : The role of chitinase-3-like protein 1 (CHI3L1) in ovarian cancer and the possible mechanisms were elucidated. CHI3L1 is a secreted glycoprotein and associated with inflammation, fibrosis, asthma, extracellular tissue remodeling and solid tumors. Our previous study showed CHI3L1 could be a potential prognostic biomarker for epithelial ovarian cancer and could protect cancer cells from apoptosis. Therefore, clinical data and quantitation of CHI3L1 of ovarian cancer patients, tumor spheroid formation, side-population assays, Aldefluor and apoptotic assays, ELISA, RT-PCR, immunoblotting and animal experiments were performed in two ovarian cancer cells lines, OVCAR3 and CA5171, and their CHI3L1-overexpressing and -knockdown transfectants. High expression of CHI3L1 was associated with poor outcome and chemoresistance in ovarian cancer patients. The mRNA expression of CHI3L1 in CA5171 ovarian cancer stem-like cells was 3-fold higher than in CA5171 parental cells. CHI3L1 promoted the properties of ovarian cancer stem-like cells including generating more and larger tumor spheroids and a higher percentage of ALDH + in tumor cells and promoting resistance to cytotoxic drug-induced apoptosis. CHI3L1 could induce both the Akt (essential) and Erk signaling pathways, and then enhance expression of β-catenin followed by SOX2, and finally promote tumor spheroid formation and other properties of ovarian cancer stem-like cells. OVCAR3 CHI3L1-overexpressing transfectants were more tumorigenic in vivo, whereas CA5171 CHI3L1-knockdown transfectants were not tumorigenic in vivo . CHI3L1 critically enhances the properties of ovarian cancer stem-like cells. CHI3L1 or CHI3L1-regulated signaling pathways and molecules could be potential therapeutic targets in ovarian cancer.